(untitled) (Revista Innova Educación, 2023)
Currently, the educational system demands active and participatory methodologies that favor motivation, divergent thinking and student inclusion, and the principles of accessibility and equality in education must be guaranteed in order to promote quality education. In this sense, students with special educational needs emerge, who present great socio-educational vulnerability, given their personal characteristics. The objective of this research is to identify, through a systematic review, the different methodologies to promote motivation and inclusion of students with special educational needs. Therefore, a search for articles was carried out in different international databases, such as Web of Science, Scopus, PsycINFO, MEDLINE ProQuest, as well as in the national electronic resource Dialnet. Thus, a total of 286 documents were obtained and, after applying the established criteria, 7 studies remained for review. The results conform a sample of 33.679 students with specific educational support needs, derived from special educational needs, motor or intellectual disability, as well as autism spectrum disorder. Consequently, the personalization of teaching should facilitate sensory channeling through the use of innovative resources that contribute to the inclusion and motivation of students. In conclusion, further intervention studies are suggested to verify the findings presented in this research.